2003
DOI: 10.1074/jbc.m300319200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Human Lung CYP2F1 Gene and Identification of a Novel Lung-specific Binding Motif

Abstract: The CYP2F1 gene encodes a cytochrome P450 enzyme capable of bioactivating a number of pulmonary-selective toxicants. The expression of CYP2F1 is highly tissue-selective; the highest expression is observed in the lung with little or no hepatic expression. The objective of these studies was to elucidate the mechanisms that govern the unique tissue-specific regulation of CYP2F1. Cosmid and bacterial artificial chromosome clones were screened and sequenced to identify a gene that spanned 14 kbp containing 10 exons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 45 publications
2
21
1
Order By: Relevance
“…2, was similar in the two cell types. This result contrasts with the finding of a study using a different gene, CYP2F1, a gene that is also lung-selective; there, promoter constructs were active in BEAS-2B cells but silent in HepG2 cells (Carr et al, 2003). In the present study, the 134-bp and 216-bp CYP2A13 promoter constructs were the most active; for the other constructs, activities decreased as the length of the promoter molpharm.aspetjournals.org fragment increased.…”
Section: Resultscontrasting
confidence: 56%
“…2, was similar in the two cell types. This result contrasts with the finding of a study using a different gene, CYP2F1, a gene that is also lung-selective; there, promoter constructs were active in BEAS-2B cells but silent in HepG2 cells (Carr et al, 2003). In the present study, the 134-bp and 216-bp CYP2A13 promoter constructs were the most active; for the other constructs, activities decreased as the length of the promoter molpharm.aspetjournals.org fragment increased.…”
Section: Resultscontrasting
confidence: 56%
“…The preferential expression of CYP2A13 and CYP2F1 transgene mRNAs in the respiratory tract is comparable to the respiratory tract-predominant expression reported previously for CYP2A13 (Su et al, 2000;Wong et al, 2005) and CYP2F1 (Carr et al, 2003) transcripts in humans. It was reported that CYP2A13 is expressed at appreciable levels in human bladders (Nakajima et al, 2006).…”
Section: Discussionsupporting
confidence: 57%
“…CYP2F1, which is the least well characterized of the three human P450s, is expressed primarily in the respiratory tract (Carlson, 2008;Zhang and Ding, 2008;Weems et al, 2010). Little CYP2F1 mRNA expression was detected in other tissues (Carr et al, 2003). Studies using mammalian cells containing low levels of heterologously expressed CYP2F1 suggested that CYP2F1 is active toward several pulmonary toxicants, including naphthalene, styrene, 3-methylindole, and benzene (Nakajima et al, 1994;Lanza et al, 1999;Powley and Carlson, 2000); however, heterologous expression of CYP2F1 in nonmammalian systems yielded nonfunctional P450 proteins (e.g., Baldwin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Electrophoretic Mobility Shift Assay. Nuclear extracts from A549 or HepG2 cells and human lung tissues were prepared as described previously (Carr et al, 2003). EMSA was performed using the gel-shift assay system from Promega essentially as described by the manufacturer.…”
Section: Nested Deletionsmentioning
confidence: 99%
“…The protein/DNA complexes and unbound probes were separated by nondenaturing gel electrophoresis using 4% polyacrylamide gels (1-8 V/length in centimeters) and detected by autoradiography. Double-stranded oligonucleotides comprising the consensus binding sequences for AP1, NFB, Sp1, OCT1, and the 2F1-LSF (Carr et al, 2003) were included (175-fold molar excess) as nonspecific competitors in the gel shift assay system (Promega). Sequence-specific competitive oligonucleotides (1-11, Table 3) were generated by mutating five base pairs at a time, using the conversion of AϾC and TϾG; competitors M9 to M55 (Table 3) contain single base pair mutations corresponding to the distance 5Ј-to 3Ј within the 57-bp insertion; and E-box knockout competitors were created by converting the consensus sequence (CACCTG) to a sequence that is not known to bind any transcription factor (AAAAT).…”
Section: Repression Of Cyp3a4 Transcription In Lung 517mentioning
confidence: 99%